A Study on Low Performing Students Perception towards Mathematics: A Case of Secondary Level Community School Students of Nepal - Kunwar, Rajendra (Researcher: A Research Journal of Culture and Society, 2021)
The students' perception of mathematics is equally important for the parents as well as the teachers to deal with them effectively. Therefore, this study is concerned with the secondary level low-performing students' perception of mathematics and its effects on their achievements. The study is based on the mixed-method survey research design consisting of 312 grade IX and X students, 119 male and 193 female students from the 10 community schools of Province No. 1, Nepal. A Likert-type survey questionnaire, 'Perception Towards Mathematics Inventory (PTMI) was developed and administered by the researchers to the participants. Thus, the collected quantitative data were analyzed by using descriptive statistics. The qualitative data collected through semi-structured interviews were summarized and analyzed categorically in high-performing and low-performing groups. The findings revealed that the perception of the low-performing students towards mathematics was found negative or they did not prefer to learn mathematics. Similarly, the student's perception of mathematics was found to have a greater effect on their achievement. The group of higher achiever students was found more positive and confident towards mathematics and the lower achievers were found negative and anxious. However, most of the students were found aware of the value of mathematics.